Intervensi Nutrisi pada Kualitas Hidup Lansia Penderita Diabetes Melitus 2: (Literature Riview) - Uchira Uchira; Sriwanti Amba Bunga (Jurnal Siti Rufaidah, 2026)
Type 2 diabetes mellitus in the elderly significantly impacts quality of life (QoL) due to physiological changes in aging, comorbidities,and the risk of chronic complications. Nutritional management is considered a key intervention to improve glycemic control and functional status in the elderly.Objective: To review the current evidence regarding the effect of nutritional interventions on the quality of life in elderly with type 2 diabetes mellitus through a Literature Review approach.Methods: The Literature Review was conducted by identifying articles from the Scopus database published in 2020–2025. The review process included screening based on inclusion-exclusion criteria, eligibility assessment, and narrative synthesis of relevant studies,including controlled trials,quasi-experimental studies, observational studies, and systematic observations.Results: From the selected studies, interventions with a low glycemic index diet and a balanced diet have been shown to reduce HbA1c levels and the risk of complications; a multicomponent program combining diet and exercise produces synergistic effects on glucose control, physical function,and quality of life.Structured nutrition education (DSME) and family involvement improve satisfaction and metabolic outcomes.The use of technology (mobile apps) shows potential in monitoring intake and glucose,although digital literacy challenges and limited sample size and study design are often limitations.Conclusion: Targeted nutrition interventions, especially when combined with exercise, education,family support,and age-friendly technology,have the potential to improve metabolic control and quality of life in older adults with T2DM.Recommendation: Large-scale RCTs and more robust longitudinal studies are needed to establish the long-term effectiveness and cost-effectiveness of multicomponent nutrition interventions and technology adaptations for older adults with multimorbidity.